Rearing and Spawning Technique of Clown Loach (Chromobotia macracanthus, Bleeker 1852) in Research Institute for Ornamental Fish Culture of Depok, Indonesia - Mita Winarti; Asep Permana; Darmawan Setia Budi (IJOTA (Indonesian Journal of Tropical Aquatic), 2020)
The high demand of botia fish (Chromobotia macracanthus) in the market lead to its sustainability in nature being threatened. The purpose of this technical report is to describe the broodstock and spawning techniques of botia fish carried out at the Research and Cultivation Center for Freshwater Ornamental Fish (BRBIH) Depok, West Java. This activity was carried out from December 2019 to January 2020. This study used two female cows with a spawning ratio of 3 : 1. The average length of the female parent is 9.5 cm with an average weight of 33.5 g, while the length of the male parent is 15.3 cm with an average weight of 56.3 g. Spawning is done artificially using ovaprim. The result of this study was the fecundity value of an average of 8 453 eggs / ind. The average FR was 86.15 %, and the average HR was 78.15 %.